Eligibility assessment, covariate assessment, and follow-up windows relative to time 0 for the cohort design. - Shelby S. Fisher (22676406) (2025)
AE = adverse event; COVID-19 = coronavirus disease 2019; LTC = long-term care; SNF = skilled nursing facility. a Gaps in insurance coverage of a maximum of 31 days were permitted in MarketScan. b Pregnancy status identified in MarketScan only. c Outcome-specific washout windows were applied only to analyses of individual AEs, not to the base study cohort. d Bell’s palsy and encephalitis/encephalomyelitis. e All outcomes other than Bell’s palsy and encephalitis/encephalomyelitis. f Occurrence of the event of interest or censoring at the earliest of the following: disenrollment from the database (gaps in insurance coverage of a maximum of 31 days were permitted in MarketScan); death (available in Medicare only); end of the study period (10 December 2020); or the day before COVID-19 diagnosis in comparators for both the comparator and the individual with COVID-19 to whom they were matched. Follow-up for the cohort design was not censored at the end of the 41-day risk window as was done for the self-controlled risk interval design. Note: The cohort entry period (the time during which all Time 0 dates must occur) began on 1 April 2020, but lookback periods may have extended before 1 April 2020, as far back as 2 April 2019. Note: This figure displays the analyses with follow-up starting on the day after Time 0, and Time 0 included in the washout windows. Additional analyses were performed with follow-up beginning on Time 0, and the washout windows ending on the day before Time 0.